THE EFFECTIVENESS OF GROUP COUNSELING USING COGNITIVE RESTRUCTURING TECHNIQUES TO REDUCE PHUBBING BEHAVIOUR AT CHRISTIAN JUNIOR HIGH SCHOOL 1 SURAKARTA - Elisabeth Sari Ditaningrum; Naharus Surur; Rian Rokhmad Hidayat (Jurnal Profesi Keguruan, 2024)
Phubbing is a behavior that does not respect the other person by choosing to focus on playing with a smartphone when the other person invites him to communicate. Phubbing when done continuously will damage the quality of social relationships. The aimed of this research is to test the effectiveness of cognitive restructuring technique group counseling to eradicate phubbing behavior in class VIII students of SMP Kristen 1 Surakarta in the 2023/2024 academic year. This experimental study used Nonequivalent Control Group Design. The research subjects were 14 class VIII students of SMP Kristen 1 Surakarta who were divided into two groups, namely 7 students in the experimental group and 7 students in the control group. Data collection used a closed questionnaire on phubbing behavior to obtain pretest and posttest scores. The experimental group was given cognitive restructuring technique group counseling treatment and the control group was given group counseling without a specific approach and technique. Each group was given treatment for two meetings. The results of the analysis using the Mann Whitney test showed a significance value of 0.395 (0.395 > 0.05) on the pretest score, which means there is no significant difference in the initial condition of the pretest score of phubbing behavior, while the posttest score gets a significance value of 0.008 (0.008 <0.05) which means there is a significant difference from the posttest score between the experimental group and the control group. The difference in scores is the result of providing cognitive restructuring technique group counseling treatment to the experimental group. The Gain score results in the experimental group, namely an average of 7.85 and the control group an average of 3.14. It is known that the average gain score is higher in the experimental group that received cognitive restructuring technique group counseling treatment. This means that cognitive restructuring technique group counseling is effective in eradicating phubbing behavior.